The effects of a slope angle, inversion strength and the eddy transfer coefficient on katabatic winds - Ingibjörg Jóhannesdóttir 1994- (2019)
The purpose of this research is to view the effects of a slope angle, inversion strength and the eddy transfer coefficient on katabatic winds. An equation for downslope motion is used to see how much the wind speed changes with time and then the wind speed after three hours is compared with observed wind speed at three locations in Iceland; Sauðárkrókur Airport, Staðarhóll and Eyrarbakki. The results show that the calculated wind speeds in Sauðárkrókur Airport and Staðarhóll are considerably higher than the observed wind speeds. That is considered to be because the eddy transfer coefficient is in reality larger than was estimated and the slope angles are in reality inhomogeneous. The calculated wind speeds in Eyrarbakki are lower than the observed wind speeds, the cold northerly flow may be as much a land-breeze as a katabatic wind. Tilgangurinn með þessu verkefni er að skoða áhrif halla landslags, styrk hitahvarfs og kvikustreymisstuðuls á fallvinda. Jafna sem lýsir hreyfingu loftmassa undan halla er leidd út og notuð í þeim tilgangi að skoða hvernig hraðinn breytist með tíma. Hraðinn eftir þrjár klukkustundir er skoðaður og borin saman við mældan vindhraða á þrem stöðum á Íslandi; flugvelli Sauðárkróks, Staðarhóli og Eyrarbakka. Niðurstöður sýna að fræðilegur vindhraði á flugvelli Sauðárkróks og Staðarhóli er töluvert meiri en mældur vindhraði. Þessi munur er talinn vera vegna þess að kvikustreymisstuðullinn er í raun hærri en gert var ráð fyrir og halli landslags er ójafn. Fræðilegur vindhraði á Eyrarbakka er minni en mældur, norðlæga vindáttin gæti allt eins verið landgola eins og fallvindur.